Dual Isotope SPECT Study With Epilepsy Patients Using Semiconductor SPECT System. (September 2017) - Shiga, Tohru; Suzuki, Atsuro; Sakurai, Kotarou; Kurita, Tsugiko; Takeuchi, Wataru; Toyonaga, Takuya; Hirata, Kenji; Kobashi, Keiji; Katoh, Chietsugu; Kubo, Naoki; Tamaki, Nagara
Abstract : Purpose: We developed a prototype CdTe SPECT system with 4-pixel matched collimator for brain study. This system provides high-energy-resolution (6.6%), high-sensitivity (220 cps/MBq/head), and high-spatial-resolution images. The aim of this study was to evaluate dual-isotope study of CBF and central benzodiazepine receptor (BZR) images using 99m Tc-ECD and 123 I-IMZ with the new SPECT system in patients with epilepsy comparing with single-isotope study using the conventional scintillation gamma camera. Methods: This study included 13 patients with partial epilepsy. The BZR images were acquired at 3 hours after 123 I-IMZ injection for 20 minutes. The images of IMZ were acquired with a conventional 3-head scintillation gamma camera. After BZR image acquisition with the conventional camera, 99m Tc-ECD was injected, and CBF and BZR images were acquired simultaneously 5 minutes after ECD injection with the new SPECT system. The CBF images were also acquired with the conventional camera on separate days. The findings were visually analyzed, and 3D-SSP maximum Z scores of lesions were compared between the 2 studies. Results: There were 47 abnormal lesions on BZR images and 60 abnormal lesions on CBF images in the single-isotope study with the conventional camera. Dual-isotope study with the new system showed concordant abnormal findings of 46 of 47 lesions on BZR and 54 of 60 lesions on CBF images with the single-isotope study with the conventional camera. There was high agreement between the 2 studies in both BZR and CBF findings (Cohen κ values = 0.96 for BZR and 0.78 for CBF). In semiquantitative analysis, maximum Z scores of dual-isotope study with the new system strongly correlated with those of single-isotope study with the conventional camera (BZR: r = 0.82, P < 0.05, CBF: r = 0.87, P < 0.05). Conclusions: Our new SPECT system permits dual-isotope study for pixel-by-pixel analysis of CBF and BZR information with the same pathophysiological condition in patients with epilepsy.